Evaluating the Relationship between Budget Revenues and Expenditures in Iran - Mohamad Taghi Fayazi; Shahin Javadi (پژوهش‌های برنامه و توسعه)
In order to adopt the appropriate fiscal policy, one should know the correct relationship between the revenues and expenses of the government. The main goal of this study is to offer appropriate policy recommendations to reduce the budget deficit and resolve the imbalance between the government's revenues and expenses. In this research, the dynamic relationship and mutual effects between government revenues and government expenditures have been tested using the vector error correction (VEC) model. The results confirm the Tax-and-Spend Hypothesis for Iran. The political consequence of this hypothesis for Iran is that higher tax revenues lead to higher expenditures, which can cause an increase in the inflation rate and financial illusion in addition to the government's failure to resolve the budget deficit. Therefore, the government's efforts should be accompanied by appropriate reforms in public spending to enable productive investments and, as a result, sustainable economic growth. With increasing economic growth in the long term, it will be possible to increase tax revenues in order to compensate for the budget deficit.